Japanese-speaking Politeness Used in Hotaru no Hoshi Movie Through The Study of Sociolinguistic - Agustina, Istiqomah Dewi (Universitas Negeri Semarang, 2018)
The purpose of this research is to found out the Japanese-speaking politeness that used by Japanese people in social interaction. This research also intent on knowing about language in use, especially the structure of honorifics in use to expressing Japanese-speaking politeness. This research use descriptive-qualitative approach. The data consist of conversation dialogues, based on social rules of politeness when Japanese people interact each other. This data originated from Japanese movie “Hotaru no Hoshi” that direct by Hiroshi Sugawara. Data was collected by observing use of language in conversations while make a note without involve those conversations. Data was analyzed by “padan ekstralingual” method and study of sociolinguistics. The result of data analysis explain that Japanese-speaking politeness was expressed by: greeting the addressee with appropriate name (with titles or professional ranks); using polite language (teineigo) when speaking in a formal setting; using sentence final particle “ne” (isn’t it?) to show empathy toward addressee; and use of polite language to manipulate psychological attitude toward the other participants.